TRANSFORMATIONAL LEADERSHIP STRATEGY OF SCHOOL PRINCIPALS IN IMPLEMENTING ACADEMIC SUPERVISION TO BUILD A QUALITY CULTURE - Holisoh, Iis; Hasani, Aceng; Jakaria, Jakaria (Universitas Labuhanbatu, 2026)
Purpose – This study aims to examine the transformational leadership strategy employed by the school principal in implementing academic supervision as a means of building a quality culture at SD Negeri Patia 1, Pandeglang Regency.Methodology – A qualitative case study design was adopted. Research participants included the school principal, teachers, school committee members, and students, selected through purposive and snowball sampling. Data were collected through in-depth interviews, non-participant observation, and documentation, and subsequently analyzed through data reduction, data display, and conclusion drawing in an interactive process guided by thematic coding.Findings – The findings reveal that the principal integrates scheduled and reflective structural supervision with cultural supervision enacted through the BERAKSI Learning Community and the internalization of the 10 Budaya Malu (Ten Cultures of Shame). Leadership manifested through role modeling, open communication, encouragement of innovation, and consistency between values and actions has cultivated a school culture characterized by reflection, collaboration, discipline, and continuous improvement.Contribution – These findings affirm that transformational leadership can reposition supervision from a mechanism of administrative control to one of professional empowerment, with substantive implications for consolidating the school's quality culture.